Perancangan dan Penerapan Sistem Informasi Maintenance di PT. XYZ untuk Mengukur Kinerja Mesin - Joni Apriyanto (Yayasan Literasi Sains Indonesia, 2024)
Manufacturing business competition is increasingly competitive. Companies will survive if they are efficient in their operations and are able to maximize the utility of their production machine capacity. Machine utility can be maximized if the machine is always ready for production properly. PT. XYZ is a printing company. The problems at PT. XYZ include the cessation of the production process due to machine damage and machine performance has not been measured because the machine history database is still done manually. The purpose of this study is to design an integrated machine maintenance and repair information system that helps technicians when making repairs and is able to monitor and evaluate machine performance and the performance of the engineering department. The method used in this study is to conduct a survey of the existing system and plan a system that is able to analyze machine conditions in detail. The result of this study is a maintenance information system that can be used well at PT. XYZ. This system is able to assess machine performance and the performance of the engineering department and is able to be a reference when repairs and the report data can be used to plan maintenance and development of the engineering team.